Anti-inflammatory mechanisms of the annexin A1 protein and its mimetic peptide Ac2-26 in models of ocular inflammation in vivo and in vitro - Girol, Ana P. [UNESP]; Mimura, Kallyne K. O.; Drewes, Carine C.; Bolonheis, Simone M.; Solito, Egle; Farsky, Sandra H. P.; Gil, Cristiane D.; Oliani, Sonia Maria [UNESP] (Oxford University Press (OUP), 2013)
Annexin A1 (AnxA1) is a protein that displays potent anti-inflammatory properties, but its expression in eye tissue and its role in ocular inflammatory diseases have not been well studied. We investigated the mechanism of action and potential uses of AnxA1 and its mimetic peptide (Ac2-26) in the endotoxin-induced uveitis (EIU) rodent model and in human ARPE-19 cells activated by LPS. In rats, analysis of untreated EIU after 24 and 48 h or EIU treated with topical applications or with a single s.c. injection of Ac2-26 revealed the anti-inflammatory actions of Ac2-26 on leukocyte infiltration and on the release of inflammatory mediators; the systemic administration of Boc2, a formylated peptide receptor (fpr) antagonist, abrogated the peptide's protective effects. Moreover, AnxA1-/- mice exhibited exacerbated EIU compared with wild-type animals. Immunohistochemical studies of ocular tissue showed a specific AnxA1 posttranslational modification in EIU and indicated that the fpr2 receptor mediated the anti-inflammatory actions of AnxA1. In vitro studies confirmed the roles of AnxA1 and fpr2 and the protective effects of Ac2-26 on the release of chemical mediators in ARPE-19 cells. Molecular analysis of NF-κB translocation and IL-6, IL-8, and cyclooxygenase-2 gene expression indicated that the protective effects of AnxA1 occur independently of the NF-κB signaling pathway and possibly in a posttranscriptional manner. Together, our data highlight the role of AnxA1 in ocular inflammation, especially uveitis, and suggest the use of AnxA1 or its mimetic peptide Ac2-26 as a therapeutic approach. Copyright © 2013 by The American Association of Immunologists, Inc.
Keywords: acetyl alanylmethionylvalylserylphenylalanylleucyllysylglutaminylalanyltryptophylphenylalanylisoleucylglutamylasparaginylglutamylglutamylglutaminylglutaminylglutamyltyrosylvalylglutaminylthreonylvalyllysine; antiinflammatory agent; cyclooxygenase 2; formylpeptide receptor; immunoglobulin enhancer binding protein; interleukin 1beta; interleukin 6; interleukin 8; lipocortin 1; tumor necrosis factor alpha; unclassified drug; animal experiment; antiinflammatory activity; blood vessel permeability; cell count; cell infiltration; cell migration; controlled study; cytokine release; drug efficacy; drug mechanism; immunohistochemistry; immunoreactivity; leukocyte; male; neutrophil; nonhuman; priority journal; protein expression; protein function; protein phosphorylation; protein processing; rat; treatment response; uveitis; Animals; Annexin A1; Anti-Inflammatory Agents; Aqueous Humor; Cyclooxygenase 2; Cytokines; Disease Models, Animal; Endotoxins; Gene Expression Regulation; Lipopolysaccharides; Male; Mice; Mice, Knockout; Models, Biological; Neutrophil Infiltration; Neutrophils; NF-kappa B; Oligopeptides; Peptides; Phosphorylation; Protein Transport; Rats; Receptors, Formyl Peptide; Uveitis